Antibiofilm effects of punicalagin against Staphylococcus aureus in vitro - Xu, Yunfeng; Guo, Weiping; Luo, Denglin; Li, Peiyan; Xiang, Jinle; Chen, Junliang; Xia, Xiaodong; Xie, Qinggang (Frontiers in Microbiology, 2023)
Staphylococcus aureus is a common foodborne pathogen which can form biofilms to help them resist to antimicrobials. It brings great harm to human health. Punicalagin has good antimicrobial activities against S. aureus, but its effect on biofilm formation has not been clearly illustrated. The aim of this study was to explore the antibiofilm effects of punicalagin against S. aureus. Results showed that punicalagin did not significantly interfere with the growth of S. aureus at the concentrations of 1/64 MIC to 1/16 MIC. The biomass and metabolic activity of biofilms were significantly reduced when exposed to sub-inhibitory concentrations of punicalagin. The number of viable cells in the biofilms was also decreased after punicalagin treatment. Scanning electron microscopy and confocal laser scanning microscopy images confirmed that punicalagin damaged the structure of biofilms. The antibiofilm mechanism was partly due to the modification of the cell surface which led to the reduction of cell surface hydrophobicity. These findings suggest that punicalagin has the potential to be developed as an alternative to control S. aureus biofilms.